The drone delivery services: An innovative application in an emerging economy - Nguyen Thi Khanh Chi; Le Thai Phong; Nguyen Thi Hanh (Asian Journal of Shipping and Logistics (AJSL), 2023)
The rapid development of the Internet of Things (IoT) devices led to new era in the maritime and road transportation industry and research. This article studies the critical determinants of Drone delivery services (personal innovativeness, outcome expectancy, positive anticipated emotions, and perceived risk) on customer willingness to use Drone in an emerging economy. The article employs correlation analysis and structural equation modeling (SEM) to analyze the data of 602 valid observations collected in the structured questionnaire survey in Vietnam. Empirical results indicate that outcome expectancy and personal innovativeness positively impact customer attitude and anticipated emotion, while outcome expectancy has the strongest influence. These findings also show that outcome expectancy and personal innovativeness have an effect on customer willingness to use Drone through their positive attitude and positive anticipated emotions. Interestingly, the perceived risk of Drone is considered a moderator in reducing the relationship between customer attitude and willingness to use Drone while it has an insignificant impact on customer emotion and willingness to use.
Keywords: 650; Customer attitude; Drone delivery service; Outcome expectancy; Perceived risk